Koordinasi Pelayanan E-Ktp di Kecamatan Kiaracondong Kota Bandung - Imas Sumiati; Nadia Putri Meirina (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research was conducted to determine the coordination of making E-KTPs provided by the government. Apart from that, this research was also carried out to find out the factors that constrain the E-KTP making service system which can be seen from the lack of availability of blanks and the public's lack of understanding regarding technology. In service procedures, the research using a qualitative case study approach by collecting data obtained from observations and interviews. The results of this research show that the service system for making E-KTP is still not optimal, which can be seen starting from the uncertain service certainty, as well as there are still delays in printing, where there is a lack of blank availability and there are still people who do not understand the technology.